The Potential of Ironwood as an Activated Carbon Adsorbent for Heavy Metal Mercury (Hg) Using the Pyrolysis Method - Zimon Pereiz; Efriyana Oksal; Chuchita Chuchita; Miranti Maya Sylvani; Yunus Pebriyanto (Jurnal Sains dan Terapan Kimia, 2025)
This study focuses on the utilization of ironwood as an activated carbon adsorbent to remove heavy metal mercury (Hg). The background of the problem includes mercury pollution from various industrial sources and its harmful impacts on the environment and human health. The purpose of this study was to develop an effective method for adsorbing mercury using natural ironwood materials. The research method involves the synthesis of activated carbon through pyrolysis and chemical activation processes, followed by a series of adsorption tests on mercury with variations in pH conditions, contact time, and acid concentration. The research data showed that the optimum adsorption capacity was achieved at a mercury concentration of around 500 ppm, with high adsorption efficiency at pH 1 and a contact time of 80 minutes. The results also showed that the adsorption kinetics followed a second-order model with a rate of 0.017119 g/mg.min. In conclusion, the mercury adsorption process using activated carbon from ironwood followed the Langmuir isotherm model, with an adsorption capacity of 63.036 mg/g, indicating that the adsorbent had been successfully synthesized and had an effective ability to remove mercury.